Spectrophotometric Determination Of Nitrazepam And Dapson Using Vanillin Reagent in Pharmaceutical Preparations - Maha Al-Obaidi; Theiaa Al-Sabha; Thabit Al-Ghabsha (College of Education for Pure Sciences, 2014)
A simple, sensitive and selective spectrophotometric method is described for the determination of dapson and nitrazepam in bulk drug and in dosage forms using vanillin as the chromogenic agent. The method is based on the condensation reaction between dapson (DN) and reduced nitrazepam (RNZ) with vanillin to produce an intense yellow colored product. The resulting Schiff's bases show an absorption maximum at 405 nm for both drugs. Beer's law was obeyed in the concentration range 1-30 and 1-20 µg/ml with a molar absorptivity of 8.69×103 and 1.332×104 L mol-1 cm-1 for DN and RNZ respectively. The limit of detection (LOD) and limit of quantification (LOQ) were found to be 0.087 and 0.299 µg/ml for DN, respectively and 0.069 and 0.231 µg/ml for RNZ, respectively. The method shows good accuracy and precision, and was applied successfully to the determination of DN and RNZ in tablets. No interference was observed from common additives found in pharmaceutical preparations. The results obtained by the proposed method were validated statistically by comparing the results with those of official methods by applying the Student's t-test and F-test.